Wear and Corrosion Behaviour of Copper Oxide Doped Hydroxyapatite Thin Film Layer Coated By PLD - Vangölü, Sebahattin Yenal (Fırat University, 2021)
Researches on improving osseointegration which is defined as a direct bond formation between living bone and implant and reducing bacterial growth on the material, are still among the studies that engage scientists’ attention. While hydroxyapatite coating is one of the most widely used approaches to increase osseointegration, methods used to reduce bacterial growth vary. One of these methods is to form a copper-doped hydroxyapatite layer on the implant, which is known to be antibacterial. In this study, a copper oxide-containing hydroxyapatite thin film layer (HA/CuO) was formed on the surface of 316L stainless steel by using pulsed laser deposition (PLD). Dry sliding wear behaviour and corrosion behaviour of untreated and coated samples were comparatively investigated in PBS (phosphate buffer saline) and SBF (simulated body fluid) after coating. Structural characterizations were examined with SEM and XRD.

Canlı kemik ve implant arasındaki doğrudan bağ oluşumu olarak tanımlanan osseointegrasyonu iyileştirme ve malzeme üzerinde bakteri oluşumunu azaltma üzerine yapılan araştırmalar bilim dünyasının en güncel çalışmalardandır. Osseointagrasyonu artırmada en çok kullanılan yöntemlerden biri hidroksiapaptit kaplamalarken, bakteri oluşumunu azaltmada kullanılan yöntemler çeşitlilik göstermektedir. Bu yöntemlerden biri de antibakteriyel olduğu bilinen bakır oksitin hidroksiapatit içerisine gömüldüğü kaplamalardır. Bu çalışmada, 316L paslanmaz çelik yüzey üzerine pulsed laser deposition (PLD) işlemi uygulanarak yüzeyde bakır içerikli hidroksiapatit ince film tabakası (HA/CuO) oluşturulmuştur. Kaplama işlemi sonrası işlemsiz ve kaplanmış numunelerin PBS (phosphate buffer saline) ve SBF (yapay vücut sıvısı) içerisinde korozyon davranışları ve kuru ortam aşınma davranışları karşılaştırılmıştır. Yapısal karakterizasyonları SEM, XRD ve 3D profilometre kullanılarak gerçekleştirilmiştir.
PLD Yöntemiyle Kaplanmış Bakır Oksit İçerikli Hidroksiapatit İnce Filmin Aşınma ve Korozyon Davranışı
Keywords: Engineering; Mühendislik